Reliability of Resistivity Method of Prospecting Groundwater in Hard Rock Region - Bhagyawant, R G; Dhotre, R S; Gorantiwar, S D; Kamble, K J (Journal of Agricultural Engineering, 2007)
A study was conducted to determine the reliability of electrical resistivity method of ground water explorations at ’farmers’ field in under hard rock region in Rahuri Tahsil of district Ahmednagar (Maharashtra). In this method, vertical electrical soundings with Schlumberger array were carried out at forty locations in the area. The data gathered from this method at each sounding were interpreted by curve break method for finding the depth of soil formations. The interpreted data were compared with the actual observations recorded during the drilling process at 15 locations. The method was found effective in hard rock areas, as the average deviation between observed and estimated depth of water bearing strata was found to be 13.45 per cent. The reliability of this method was found 73% for selecting the site for irrigation water and 87% for determining the depth of water bearing formation.